OPTIMASI FERMENTASI ISOLAT Actinomycetes TERHADAP PERTUMBUHAN BAKTERI Salmonella typhi SECARA IN VITRO - Anisa Sri Mulyani (2023)
Actinomycetes are long rod-shapes bacteria, Gram positive and can used as antimicrobial because it can produce secondary metabolites. Factors that affect production of these compounds are fermentation time and pH. Salmonella typhi is pathogenic bacteria that causes typhoid fever. This study aims to determine optimization time by controlling pH of Actinomycetes isolates on the growth of S.typhi bacteria in vitro. Type and research design used was a true experimental study and a completely randomized design (CRD). Medium used to process Actinomycetes isolates is Starch Casein Agar (SCA) and then fermented in media containing 2% mannitol, 2% peptone and 1% glucose and incubated for 1, 2 and 3 days. Antimicrobial activity test method in this study used well method on Nutrient Agar (NA) media. Actinomycetes bacteria with fermentation time on 1, 2 and 3 days accompanied by pH control can inhibit growth of S.typhi bacteria with an average inhibition zone formed of 13,70 mm; 15,41 mm and 15,09 mm. Kruskal Wallis test showed a significant difference in the inhibition zone in each treatment group. Second day of fermentation group has greatest antimicrobial effectiveness with an average inhibition cone value of 15.41 mm. Mechanism of antimicrobial activity includes inhibiting protein synthesis, inhibiting cell wall and inhibiting bacterial DNA synthesis. Keywords: Actinomycetes, antimicrobial, long fermentation, Salmonella typhi